2021
DOI: 10.3390/nu13103608
|View full text |Cite
|
Sign up to set email alerts
|

High Fructose Intake Contributes to Elevated Diastolic Blood Pressure in Adolescent Girls: Results from The HELENA Study

Abstract: Background: The association between high fructose consumption and elevated blood pressure continues to be controversial, especially in adolescence. The aim of this study was to assess the association between fructose consumption and elevated blood pressure in an European adolescent population. Methods: A total of 1733 adolescents (mean ± SD age: 14.7 ± 1.2; percentage of girls: 52.8%) were analysed from the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study in eight European countries. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 80 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…Parameters recognized to have an impact on modifiable cardiovascular risk factors were identified [ 19 , 56 , 57 , 58 ]. Salt, EPA + DHA, and fructose intakes will be included in the multivariate linear regression to analyze their impact on the PDAY score ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters recognized to have an impact on modifiable cardiovascular risk factors were identified [ 19 , 56 , 57 , 58 ]. Salt, EPA + DHA, and fructose intakes will be included in the multivariate linear regression to analyze their impact on the PDAY score ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meals were converted into energy and macro/micronutrient intake primarily by using the German food code and nutrient database (Bundeslebensmittelschlüssel, BLS, version II3.1). The nutrients included in the main statistical analysis for the association with the primary end point (PDAY risk score) were salt (sodium chloride total intake, present in the food and added), long-chain polyunsaturated fatty acid (LC-PUFA), including eicosapentanoic acid (EPA) and docosahexaenoic acid (DHA) (using the German food code and nutrient database), and fructose (using fructose composition analysis [ 18 , 19 ]) intake, in gram per day. Data scoring was also performed to assess the Diet Quality Index (DQI), the Healthful Plant-based Diet Index (HPDI), and the NOVA classification for ultra-processed food (UPF) consumption.…”
Section: Methodsmentioning
confidence: 99%
“…The study by Béghin et al examined the effect of consuming fructose from various dietary sources, both natural (e.g., vegetables, fruits, or honey) and industrial (e.g., cakes, confectionery, or sugar-sweetened drinks), on the level of diastolic blood pressure in young girls aged 12.5–17.5 years. It turned out that unlike fructose from natural sources, the one from industrial sources raises the value of blood pressure [ 58 ]. Studies in rats fed water enriched with fructose showed that increasing the amount of this sugar in the diet caused hypertension, hyperuricemia, and hypertriglyceridemia in the animals.…”
Section: Fructose As a Potential Factor Influencing Hyperuricemia And...mentioning
confidence: 99%
“…Regarding the assessment of daily fructose intake, the variable created by Béghin et al, [35] in the HELENA study was used. Total fructose exposure was calculated as fructose from monosaccharide form plus fructose from sucrose (0.5 × sucrose per 100 g).…”
Section: Dietary Assessmentmentioning
confidence: 99%